Animal genetics training resources: Capacity building for sustainable use of animal genetic resources in developing countries - International Livestock Research Institute (International Livestock Research Institute, 2014)
This training resource is presented in five modules. 1) Global perspectives on animal genetic resources for sustainable agriculture and food production in the tropics. This module provides some insight into the need for better use of animal genetic resources (AnGR) in the context of projected demand for food in developing countries until 2020. 2) Improving our knowledge of tropical indigenous animal genetic resources. This module makes a case for and highlights issues and methods that underpin improved understanding of the diversity in AnGR as a basis for designing conservation and sustainable utilisation of the diversity (the subject of module three). 3) Sustainable breeding programmes for tropical farming systems. This module discusses important factors to consider when designing sustainable genetic improvement programmes, especially under tropical conditions. 4) Quantitative methods to improve the understanding and utilisation of animal genetic resources This module reviews the most commonly used quantitative methods in the area of animal breeding and animal genetic resources. It primarily addresses scientists in the area of animal genetic resources in developing countries, including both faculty in universities/colleges and staff in research institutions. 5) Teaching methods and science communication. The purpose of module five is to highlight the roles and objectives of higher education, and to discuss aspects of teaching and learning. It provides examples of teaching and examination methods, as well as discussions on research supervision, science communication, evaluation of courses and curricula, and how to promote educational Development. The module addresses university/college teachers and scientists teaching animal breeding in developing countries, but large parts of the contents are general and useful also for others teaching in higher education institutions. The Cd also includes tools such as case studies, exercises, examples, compendia, breed databases, maps, clips, photographs, a virtual library, web resources, and a glossary. The modules and the tools are inter-linked to collectively form a cohesive resource.